The Evaluation of the Stability of Donan Cave, Pangandaran, West Java, Based on the Classification of Rock Mass - Ikfi Maasyi Hanif; I Gde Budi Indrawan (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2021)
Assessment of rock mass quality was conducted to estimate the stability of Donan Cave. This research involved geological mapping, cave geometry mapping, rock mass quality zoning by scanline survey based on the Q-system rock mass classification, and cave stability estimation based on the rock mass quality, ratio of cave roof thickness to width, and load. The research results indicate that Donan Cave is composed of limestone of the Kalipucang Formation. Several faults are located in the vicinity of Donan Cave. Donan Cave is dominated by good to very good quality rock masses and is estimated to be stable in a relatively long period of time. However, rock fall hazard due to dynamic load at several zones, which have relatively thin and poor-quality rock masses has to be anticipated.